2022
DOI: 10.1071/sh22039
|View full text |Cite
|
Sign up to set email alerts
|

Participatory approaches to delivering clinical sexually transmitted infections services: a narrative review

Abstract: Although sexual health programming and clinical sexually transmitted infections (STIs) services have traditionally been developed through 'top-down' approaches, there is emerging evidence that participatory approaches benefit the development and implementation of such services. Although other studies have already highlighted the benefits of participation in research and implementation of clinical STIs services delivery, this narrative review focuses on how community participation in clinical STIs services deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…A few studies reported structural level changes, including positive influences on clinic wait times, service coverage for key populations, reduced treatment stockouts, as well as the reduction or elimination of exclusionary practices. Recent narrative reviews on participatory approaches towards the delivery of clinical sexually transmitted infections services, and digital approaches to improving community engagement in clinical trials chart potential pathways towards strengthening community-led health services [54 ▪ ,55].…”
Section: Mitigating Stigma To Improve Uptake Of Hiv Servicesmentioning
confidence: 99%
“…A few studies reported structural level changes, including positive influences on clinic wait times, service coverage for key populations, reduced treatment stockouts, as well as the reduction or elimination of exclusionary practices. Recent narrative reviews on participatory approaches towards the delivery of clinical sexually transmitted infections services, and digital approaches to improving community engagement in clinical trials chart potential pathways towards strengthening community-led health services [54 ▪ ,55].…”
Section: Mitigating Stigma To Improve Uptake Of Hiv Servicesmentioning
confidence: 99%
“… 31 Increased community engagement and leadership in the design, delivery and scale-up of STBBI services may also increase uptake in these communities as well. 32 , 33 We have also found GCO to be a cost-effective alternative for HIV testing among GBM living in Vancouver, BC when compared to clinic-based HIV testing services, 34 which may encourage policy makers to consider implementing a similar service in Ontario.…”
Section: Discussionmentioning
confidence: 90%
“…Citizens have also been involved in the implementation of interventions. These include involving communities in the planning, developing, delivering, evaluating, and scaling up of clinical HIV and sexually transmitted infections services [33], as well as leveraging individual (e.g. individual community member involvement in research activities), interpersonal (e.g.…”
Section: Conceptualizing Citizen Sciencementioning
confidence: 99%